Representasi Perempuan dan Budaya Konsumen dalam Iklan Shopee 9.9 2024 - Ekawati, Sheilla; Daksa, Farrel Aditya; Azzuhdi, Abdurrohman Naufal; Sudiwijaya, Erwan (Universitas Muhammdiyah Yogyakarta, 2025)
This research analyzes the representation of women and consumer culture in the Shopee 9.9 advertisement of 2024. Using semiotic methods, this research explores how women are portrayed in the advertisement, particularly in relation to gender stereotypes. The research findings indicate that the portrayal of women reinforces conventional beauty standards and passive femininity, as well as promotes a culture of consumption through visual cues and product placement. These representations play an important role in shaping the image of femininity and shopping activities, in line with societal trends in digital consumption. This representation not only shapes society's perception of women as symbols of aesthetics but also influences consumer decisions regarding the advertised products. Moreover, the elements of consumer culture in this advertisement reflect a glamorous lifestyle, trends in luxury goods consumption, and online shopping habits as part of the modern consumer identity.